Functional constipation frequency in children diagnosed with autism spectrum disorder - Çağatay Günay; Hasret Ayyıldız Civan; Semra Yılmaz; Didem Gülcü Taşkın (Universitas Negeri Padang, 2021)
Aim: In our study, we aimed to determine the frequency of functional constipation in children diagnosed with autism spectrum disorders by child and adolescent psychiatry and mental health.Materials and Methods: Between September 2017 and September 2018, children with autism spectrum disorder who applied to BakırköySadiKonuk Education and Research Hospital Child and Adolescent Psychiatry Outpatient Clinic were evaluated by means of childhood autism rating scale (CARS). A total of 108 patients were evaluated with the Roman IV criteria and the frequency of functional constipation was investigated.Results: A total of 108 cases, 87% (n = 94) male and 13% (n = 14) female, were studied. The ages of the patients were between 2 and 15 years and the mean age was 6.89 ± 2.76. Organic constipation was not detected in patients with constipation and all of them were diagnosed as functional constipation. There was no statistically significant difference between the rates of functional constipation in cases according to gender. The incidence of functional constipation in males was significantly higher in patients with severe autism than in those with mild to moderate autism. “Two or fewer defecations in the toilet per week” criteria was found significantly higher in girls than in boys. No significant difference was found for the other five criteria according to gender. Each of the six criteria of the Rome IV criteria were found to be significantly higher in patients with severe autism than those with mild to moderate autism according to CARS scores. One of the Roman IV criteria, “History of large diameter stools that may obstruct the toilet” was found significantly higher in patients aged nine years and older. No significant correlation was found between the other criteria and age groups.Conclusion: All of the six criteria of the Roman IV criteria were significantly higher in cases with severe autism according to CARS, compared to those with mild to moderate autism.